Research and Development decisions, their importance and financing - Gulhati, Swati (2009)
This qualitative research aims to study the importance and the various methods of financing Research and Development decisions by different business companies. Research and development has long been acknowledged as central to the sustenance and growth of all entities, and most companies include R&D in their plan outlays. The study explores the need of R&D in businesses , along with the process adopted by different companies to reach their final product or service. If R&D is an important activity for the survival or functioning of a business in the market, it is crucial to understand the methods of funding such activities in both a normal economic situation and the current one of the recession. This research also attempts to understand how the consumers of the products of these companies view R&D and its affect on brand loyalty. As many as eight different companies, representative of varied business segments were chosen. Formatted questionnaires were issued to top officers including few CEO’s , in some cases open ended interviews were arranged at their locations. The research finds that R&D is perceived as extremely important by all companies and its financing is done by their own internal funds by most companies. The customers view R&D based on feedback as an acknowledgement of their aspirations and affirmed that it ensures brand loyalty. Through this study, several propositions for further research have also been identified.